Answer:
1) ![(f+g)(x)=2x^2+3x-6](https://tex.z-dn.net/?f=%28f%2Bg%29%28x%29%3D2x%5E2%2B3x-6)
2) ![(f-g)(x)=2x^2+x](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D2x%5E2%2Bx)
3) ![(f \cdot g)(x)=2x^3-4x^2-9x+9](https://tex.z-dn.net/?f=%28f%20%5Ccdot%20g%29%28x%29%3D2x%5E3-4x%5E2-9x%2B9)
Step-by-step explanation:
So we have the two functions:
![f(x)=2x^2+2x-3\text{ and } g(x)=x-3](https://tex.z-dn.net/?f=f%28x%29%3D2x%5E2%2B2x-3%5Ctext%7B%20and%20%7D%20g%28x%29%3Dx-3)
And we want to find (f+g)(x), (f-g)(x), and (f*g)(x).
1)
(f+g)(x) is the same to f(x)+g(x). Substitute:
![(f+g)(x)=f(x)+g(x)\\=(2x^2+2x-3)+(x-3)](https://tex.z-dn.net/?f=%28f%2Bg%29%28x%29%3Df%28x%29%2Bg%28x%29%5C%5C%3D%282x%5E2%2B2x-3%29%2B%28x-3%29)
Combine like terms:
![=(2x^2)+(2x+x)+(-3-3)](https://tex.z-dn.net/?f=%3D%282x%5E2%29%2B%282x%2Bx%29%2B%28-3-3%29)
Add:
![=2x^2+3x-6](https://tex.z-dn.net/?f=%3D2x%5E2%2B3x-6)
So:
![(f+g)(x)=2x^2+3x-6](https://tex.z-dn.net/?f=%28f%2Bg%29%28x%29%3D2x%5E2%2B3x-6)
2)
(f-g)(x) is the same to f(x)-g(x). So:
![(f-g)(x)=f(x)-g(x)\\=(2x^2+2x-3)-(x-3)](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3Df%28x%29-g%28x%29%5C%5C%3D%282x%5E2%2B2x-3%29-%28x-3%29)
Distribute:
![=(2x^2+2x-3)+(-x+3)](https://tex.z-dn.net/?f=%3D%282x%5E2%2B2x-3%29%2B%28-x%2B3%29)
Combine like terms:
![=(2x^2)+(2x-x)+(-3+3)](https://tex.z-dn.net/?f=%3D%282x%5E2%29%2B%282x-x%29%2B%28-3%2B3%29)
Simplify:
![=2x^2+x](https://tex.z-dn.net/?f=%3D2x%5E2%2Bx)
So:
![(f-g)(x)=2x^2+x](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D2x%5E2%2Bx)
3)
(f*g)(x) is the same to f(x)*g(x). Thus:
![(f\cdot g)(x)=f(x)\cdot g(x)\\=(2x^2+2x-3)(x-3)](https://tex.z-dn.net/?f=%28f%5Ccdot%20g%29%28x%29%3Df%28x%29%5Ccdot%20g%28x%29%5C%5C%3D%282x%5E2%2B2x-3%29%28x-3%29)
Distribute:
![=(2x^2+2x-3)(x)+(2x^2+2x-3)(-3)](https://tex.z-dn.net/?f=%3D%282x%5E2%2B2x-3%29%28x%29%2B%282x%5E2%2B2x-3%29%28-3%29)
Distribute:
![=(2x^3+2x^2-3x)+(-6x^2-6x+9)](https://tex.z-dn.net/?f=%3D%282x%5E3%2B2x%5E2-3x%29%2B%28-6x%5E2-6x%2B9%29)
Combine like terms:
![=(2x^3)+(2x^2-6x^2)+(-3x-6x)+(9)](https://tex.z-dn.net/?f=%3D%282x%5E3%29%2B%282x%5E2-6x%5E2%29%2B%28-3x-6x%29%2B%289%29)
Simplify:
![=2x^3-4x^2-9x+9](https://tex.z-dn.net/?f=%3D2x%5E3-4x%5E2-9x%2B9)
So:
![(f \cdot g)(x)=2x^3-4x^2-9x+9](https://tex.z-dn.net/?f=%28f%20%5Ccdot%20g%29%28x%29%3D2x%5E3-4x%5E2-9x%2B9)
The value would just be the answer which is 104
(f g)(x) means f(x) * g(x), so plug the value of each function in:
(x+2)(x-4)
And solve by distributing using FOIL:
Firsts: x * x = x²
Outers: x * -4 = -4x
Inners: 2 * x = 2x
Lasts: 2 * -4 = -8
Combine them all together:
x² - 4x + 2x - 8
Combine like terms (the -4x and 2x):
x² - 2x - 8
So the second to last one is correct.
Given :
The equation below can be used to determine I (simple interest) on a loan as follows :
...(1)
P is principal, r the rate of the loan, t is the length of the loan in years.
We need to find the equation to solve in terms of r. We can find the value of P.
Dividing both sides of equation (1) by rt. So,
![\dfrac{I}{rt}=\dfrac{Prt}{rt}\\\\P=\dfrac{I}{rt}](https://tex.z-dn.net/?f=%5Cdfrac%7BI%7D%7Brt%7D%3D%5Cdfrac%7BPrt%7D%7Brt%7D%5C%5C%5C%5CP%3D%5Cdfrac%7BI%7D%7Brt%7D)
So, P can be solved as :
.
12:1 means for every dollar you bet you will win 12
so 7 x 12 = 84
you would win $84, you bet 7 so net profit would be 84-7 = $77
Net profit is $77